Multidisciplinary early activity team collaboration practice in ICUs: A qualitative study - Xueqin Wang; Jie Mi; Chuanlin Zhang; Ruiying Gan; Xinyi Luo; Qinghua Zhao (PLoS ONE, 2025)
Purpose To understand the collaborative practice experience of ICU patients’ multidisciplinary early activity team members to provide a reference for formulating a scientific multidisciplinary team collaboration model. Methods Based on the phenomenological research methodology of qualitative research, in-depth interviews were conducted with 22 multidisciplinary early mobilization teams of ICU patients in nine general tertiary hospitals in China, using a purposive sampling method, Themes were then distilled. Results Three themes and six subthemes emerged from the analysis. (1) Inadequate collaboration concepts: ① manager's philosophy, ② multidisciplinary membership concept; (2) Poor team building: ① poor team structure, ② member training needs to be strengthened; (3) Imperfect team management mechanism: ① no continuous improvement measures, ② unclear incentives. Conclusion Good teamwork, which promotes early mobilization of ICU patients, is a scientifically feasible model of collaboration that should be constructed to guide the team in their work.